Confronting the Crystal Meth Epidemic: Urgent Insights and Solutions - Faisal, Muhammad Saleh (International Journal of Pathology, 2024)
Crystal methamphetamine, or "ice," poses a significant public health threat, particularly in urban areas like Peshawar, where it has gained popularity among youth as a socially accepted "party drug." This editorial examines the factors driving its use, including peer influence and social normalization, which lead to compulsive consumption and severe health consequences. The drug’s spread resembles a "contagious social virus," especially among educated and affluent young people. To address this epidemic, coordinated efforts are needed, including stricter legislation, public awareness campaigns, school-based education programs, and community support initiatives. Ongoing research is crucial for tracking trends and developing effective interventions to safeguard youth and community well-being.